2019
DOI: 10.3892/mmr.2019.10818
|View full text |Cite
|
Sign up to set email alerts
|

A novel ATRX mutation causes Smith‑Fineman‑Myers syndrome in a Chinese family

Abstract: Smith-Fineman-Myers syndrome (SFMS) is a rare inherited disorder characterized mainly by mental retardation and anomalies in the appearance of patients. SFMS is caused by a mutation in the α-thalassemia/mental retardation syndrome X-linked (ATRX) gene and has an X-linked recessive pattern. in the present study, a novel ATRX mutation was identified, and the association between its genotype and the phenotype was explored in a chinese Han family with SFMS. This study aimed to lay a foundation for prenatal diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Overall, in this case, in addition to the above symptoms, there are obvious feeding difficulties and gastrointestinal symptoms. These symptoms have been reported in other cases ( 17 , 38 ). Furuta et al found that gastrointestinal disorders were closely related to intellectual disability, cerebral palsy, epilepsy, and other neurodevelopmental disorders.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, in this case, in addition to the above symptoms, there are obvious feeding difficulties and gastrointestinal symptoms. These symptoms have been reported in other cases ( 17 , 38 ). Furuta et al found that gastrointestinal disorders were closely related to intellectual disability, cerebral palsy, epilepsy, and other neurodevelopmental disorders.…”
Section: Discussionsupporting
confidence: 84%
“…To investigate the possibility that mutant ATRX alleles were preferentially transmitted to offspring, a meta-analysis of published pedigrees with complete reporting of family structures was conducted. data on transmission of ATRX alleles for 42 mothers were extracted from papers published between 1991 and 2019 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Probands and index cases were excluded from the calculations, as well as offspring from one mosaic mother.…”
Section: Meta-analysis Of Maternal Transmission Of Atrx Mutationsmentioning
confidence: 99%
“…The chi-square test applied to our sample was P=0.29, which does not reach statistical significance. next, the analysis was limited to a subset of families where the mutations were identified, and all members of the family were genotyped (Table II) (8)(9)(10)(11)(12)(14)(15)(16)(17). A modest sex-ratio distortion was observed in favor of the male offspring, as well as transmission-ratio distortion in favor of the ATRX mutant alleles, but these did not reach statistical significance either (Table II).…”
Section: Meta-analysis Of Maternal Transmission Of Atrx Mutationsmentioning
confidence: 99%